Social attention as a cross‐cultural transdiagnostic neurodevelopmental risk marker - Thomas W. Frazier (4229593) (2021)
The primary objectives of this study were to evaluate the structure and age-related stability of social attention in English and Arabic-speaking youth and to compare social attention between children with autism spectrum disorder (ASD), other developmental disabilities (DD), and typically-developing controls. Eye-tracking data were collected from US (N = 270) and Qatari (N = 242) youth ages 1–17, including children evaluated for possible ASD. Participants viewed 44 stimuli from seven social paradigms. Fixation was computed for areas of interest within each stimulus. Latent variable models examined the structure of social attention. Generalized estimating equation models examined the effect of age, sex, culture, and diagnostic group on social attention. The best-fitting model included a general social attention factor and six specific factors. Cultural differences in social attention were minimal and social attention was stable across age (r = 0.03), but females showed significantly greater social attention than males (d = 0.28). Social attention was weaker in DD (d = −0.17) and lowest in ASD (d = −0.38) relative to controls. Differences were of sufficient magnitude across areas-of-interest to reliably differentiate DD from controls (AUC = 0.80) and ASD-only from all other cases (AUC = 0.76). A social attention dimension that represents an early-life preference for socially salient information was identified. This preference was cross-culturally consistent and stable across development but stronger in females and weaker in DD, especially ASD. Given rapid and easy-to-collect remote eye tracking administration, social attention measurement may be useful for developmental monitoring. Acquisition of population norms, analogous to height/weight/head circumference, might enhance early screening and tracking of neurodevelopment.  Other Information Published in: Autism Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/aur.2532